2011
DOI: 10.1111/j.1537-2995.2011.03192.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemolytic anemia after kidney transplantation: a prospective analysis

Abstract: Our data collected prospectively demonstrated that: 1) positive DATs occurred in 15.7% of all patients up to Day +30 after a kidney transplant; 2) the DAT positivity occurred up to Day +10 in 9.7% of all transplanted patients; 3) the majority of the transplant recipients with a positive DAT had a nonreactive RBC eluate; and 4) PLS was the cause of a positive DAT in 13.5% of patients submitted to ABO-compatible nonidentical kidney transplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…It was reported that the frequency of a positive DAT in patients after SOT varies from 17% to 70% [2]. However, the majority of the recipients with a positive DAT have a nonreactive RBC eluate [17].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the frequency of a positive DAT in patients after SOT varies from 17% to 70% [2]. However, the majority of the recipients with a positive DAT have a nonreactive RBC eluate [17].…”
Section: Discussionmentioning
confidence: 99%
“…In ABO‐mismatched solid organ transplantation the appearance of RBC antibodies is well described occurring in 17% of renal, 40% of liver, and 70% of heart–lung transplants, leading to significant hemolysis in 9, 29, and 70% of the cases, respectively . A prospective study by Achkar and coworkers found a positive DAT in 27% (10/37) of ABO‐compatible nonidentical renal transplant recipients. Of these a total of 13.5% (5/37) developed PLS.…”
Section: Discussionmentioning
confidence: 99%
“…Especially CsA as T‐cell‐specific immunosuppressant has been linked to the occurrence of PLS in some studies . However, the only prospective study on PLS in renal transplantation by Achkar and colleagues found usage of CsA not to be associated with the onset of hemolysis. Regarding PLS in intestinal transplantation CsA was only applied once.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a 10‐year retrospective search in PubMed for English‐language journal articles using key works “passenger lymphocyte syndrome.” The review yielded 63 cases (31 studies) of PLS . Of these, eight cases (four studies) were hematopoietic stem cell and 55 cases (27 studies) were organ transplants . All eight (100%) stem cell transplants and 52 (95%) organ transplants were associated with hemolysis, reflecting a strong bias for identifying or reporting PLS associated with hemolysis.…”
Section: Case Reportmentioning
confidence: 99%